2014
DOI: 10.1002/path.4446
|View full text |Cite
|
Sign up to set email alerts
|

CXCR4 expression enhances diffuse large B cell lymphoma dissemination and decreases patient survival

Abstract: The chemokine receptor CXCR4 has been implicated in the migration and trafficking of malignant B cells in several haematological malignancies. Over‐expression of CXCR4 has been identified in haematological tumours, but data concerning the role of this receptor in diffuse large B cell lymphoma (DLBCL) are lacking. CXCR4 is a marker of poor prognosis in various neoplasms, correlating with metastatic disease and decreased survival of patients. We studied CXCR4 involvement in cell migration in vitro and disseminat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
69
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(76 citation statements)
references
References 44 publications
5
69
2
Order By: Relevance
“…CXCR4 is also associated with bone marrow involvement of nodal lymphomas . Recently, CXCR4 was suggested to be an independent prognostic marker in patients with DLBCL . Furthermore, plasma cells home to bone marrow through the CXCR4–CXCL12 axis .…”
Section: Discussionmentioning
confidence: 99%
“…CXCR4 is also associated with bone marrow involvement of nodal lymphomas . Recently, CXCR4 was suggested to be an independent prognostic marker in patients with DLBCL . Furthermore, plasma cells home to bone marrow through the CXCR4–CXCL12 axis .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it is unknown whether the use of a CXCL12/CXCR4 antagonist in nodal DLBCL will result in lymphoma cell mobilization and increased spreading [8,29-32]. Very recently, CXCR4 expression was correlated to disease progression in 12 cases of primary testicular DLBCL [33] and poor survival of 94 DLBCL cases [34]. In 20 patients with non-Hodgkin lymphomas, a significant decrease in CXCR4 mRNA expression in the BM after treatment correlated with a significantly lower risk of death [35].…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with its role in NHL, CXCR4 plays an important role in enabling cell migration in DLBCL. Increased CXCR4 expression was associated with worse survival in both ABC and GCB subtypes for 468 patients treated with the standard therapy R-CHOP [163] and a separate study of 94 patients found that those positive for CXCR4 has reduced survival and increased recurrence of disease [164]. However, a smaller cohort of 70 Korean patients did not identify an association between CXCR4 expression and survival [165].…”
Section: Diffuse Large B Cell Lymphomamentioning
confidence: 99%
“…At the cellular level, strong nuclear CXCR4 staining was correlated with systemic DLBCL whereas strong cytoplasmic CXCR5 staining was correlated with CNS involvement [166]. Furthermore, hypoxia was associated with upregulation of CXCR4 protein [167] and such an increase in CXCR4 expression is believed to increase cell dissemination [164]. IHC revealed that 80% of patients had CXCR4 coexpressed with NF-κB [165], which is often mutated in DLBCL, while CXCR4 itself contains an AIDCA somatic hypermutation hotspot that is suspect to mutation [168].…”
Section: Diffuse Large B Cell Lymphomamentioning
confidence: 99%
See 1 more Smart Citation